Mental Health Problems during Pregnancy and the Postpartum Period: A Multicenter Knowledge Assessment Survey among Healthcare Providers - M. Patabendige; S. R. Athulathmudali; S. K. Chandrasinghe (Journal of Pregnancy)
Background. Mental illness related to pregnancy can have long-lasting consequences. Healthcare providers are often the most frequent medical contact with the potential for early detection of these. Objectives were to study the awareness regarding mental health problems during pregnancy and the postpartum period among healthcare providers. Methods. A cross-sectional study was carried out with healthcare providers including the nursing staff, midwifery staff, and medical officers working at obstetric wards in three tertiary care hospitals in Sri Lanka. A self-administered questionnaire assessed staff experience with mothers having mental problems, knowledge on mental health problems related to pregnancy, and knowledge about risk factors, common symptoms, and possible consequences on a five-point Likert scale from “Strongly Agree” to “Strongly Disagree.” Results. A total of 300 staff were approached and invited to participate. Only 152 responded to the questionnaire (response rate of 50.1%). Mean (SD) age was 35.8 (9.7) years and mean (SD) years of experience was 10.1 (9.1) years. Age more than 35 years of healthcare providers is associated with statistically significant (p=0.02) average knowledge scores on the consequences of maternal mental health problems. The symptom of “excessively worrying about baby’s health” had the lowest score across all three categories with an average of 34.2%. Only 42.8% have ever heard of EPDS. Overall awareness and knowledge about risk factors, symptoms, and consequences regarding pregnancy-related maternal mental health problems are generally good among the healthcare providers studied. However, some of the few aspects are not satisfactory. Health education of pregnant women, promoting regular in-service training sessions, improvement of infrastructure, and involvement of family members from the antenatal period were discussed by the majority. Conclusion. Despite good overall awareness and knowledge, application into practice with the utilization of validated assessments is poor. This may probably explain why Sri Lanka has a high prevalence of postpartum depression suggesting urgent attention.